Effect of replacing fishmeal with palm kernel meal supplemented with crude attractants on growth performance of Macrobrachium rosenbergii - Kader, Md. Abdul; Bulbul, Mahbuba; Abol-Munafi, Ambok Bolong; Sheriff, Shahreza Md; Ng, Wing Keong; Ali, Md. Eaqub; Koshio, Shunsuke (Bioflux SRL, 2018)
A 60-day feeding trial was conducted to study the effect of partial replacement of fishmeal with palm kernel meal (PKM) on growth performance and oxidative stress of Malaysian prawn, Macrobrachium rosenbergii. A closed aquaculture system with 21 fibreglass tanks with the capacity of 150 liter was used for the experiment. Five iso-energetic (19 KJ/g DM gross energy) test diets were formulated by replacing 0, 10, 20, 30 and 40% of fishmeal with PKM and labelled as PKM0, PKM10, PKM20, PKM30 and PKM40, respectively. Another two diets were prepared by the supplementation of 2% shrimp meal and 2% squid meal in PKM30 (PKM30+) and PKM40 (PKM40+) diets, respectively. Triplicate groups of 30 post-larvae (0.041±0.001 g) were stocked in previously prepared tanks and fed the test diets at the rate of 10-15% of their body weight, twice a day. The results showed that there were no significant differences (p > 0.05) in weight gain and specific growth rate of prawn fed PKM0, PKM10, PKM20 and PKM30 diets. However, the growth parameters were significantly decreased in prawn fed PKM40 diet. Supplementation of crude attractants recovered the depleted growth performances in PKM30+ and PKM40+ groups. The feed utilization parameters also followed the similar trends. The superoxide dismutase activity was similar in all the dietary treatments except in PKM30. It is concluded that 30% fishmeal can be replaced with PKM in the diets of prawn without any detrimental effects on growth performance and feed utilization. Supplementation of small amount of crude attractants such as squid meal and shrimp meal could replace 40% or more fishmeal from the diet of Malaysian prawn.